Resume of Fluoride and Caries Control in Pediatric Dentistry - Chalestori, Bahareh Hashemzadeh; Nanobashvili, Ketevan (Caucasus Journal of Health Sciences and Public Health, 2020)
Dental caries is an infectious disease in which acid produced by bacteria dissolves tooth enamel. If not halted, this process will continue through the tooth and into the pulp, resulting in pain and tooth loss. This activity can further progress to local infections (i.e. dental alveolar abscess or facial cellulitis), systemic infection, and, in rare cases, death; while simple home and primary care setting prevention measures would save health care dollars. Development of dental caries requires 4 components: teeth, bacteria, carbohydrate exposure, and time. Protective factors that help to remineralize enamel include exposing the teeth to fluoride, limiting the frequency of carbohydrate consumption, choosing less cariogenic foods, practicing good oral hygiene, receiving regular dental care, and delaying bacterial colonization.